Shadow banking, risk-taking and monetary policy in emerging economies: A panel cointegration approach - Sheunesu Zhou; Devi D. Tewari (Cogent Economics & Finance, 2019)
This study investigates the nexus between shadow banking, bank risk and monetary policy in emerging economies. The importance of this topic arises from its impact on the relationship between price and financial stability objectives of the regulator. In essence, the existence of financial market channels of monetary policy distorts the dichotomy between price and financial stability objectives of central banks. We employ panel cointegration techniques and find a negative association between monetary policy and shadow banking. Specifically, an increase in the central bank policy rate results in a decrease in shadow bank asset growth. In addition, we find a positive association between shadow banking and bank risk. Monetary policy effectiveness increases when bank risk is high. In sum, our results show that shadow banks are an element of the bank risk-taking channel of monetary policy. We suggest policy coordination between monetary and macro-prudential policy, and close monitoring of shadow banking activities to reduce risky undertakings in the financial sector.
Keywords: C33; E44; G23; 330; monetary policy; shadow banking; bank liquidity; panel cointegration; risktaking